2016
DOI: 10.1080/03630242.2016.1153020
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of maternal health care services among indigenous women in Bangladesh: A study on the Mru tribe

Abstract: Despite startling developments in maternal health care services, use of these services has been disproportionately distributed among different minority groups in Bangladesh. This study aimed to explore the factors associated with the use of these services among the Mru indigenous women in Bangladesh. A total of 374 currently married Mru women were interviewed using convenience sampling from three administrative sub-districts of the Bandarban district from June to August of 2009. Associations were assessed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 13 publications
2
35
1
Order By: Relevance
“…27 In addition, several research on Mru 27 and Santal 35 indigenous communities showed that distinctive geographic location and rural lifestyles were influential factors for their insufficient access to health care facilities, 27 as well as unhealthy behaviors leading to NCD risks. 26 Thus, unhealthy practices affect indigenous peoples' health condition and status adversely.…”
Section: Indigenous People In Bangladeshmentioning
confidence: 99%
See 2 more Smart Citations
“…27 In addition, several research on Mru 27 and Santal 35 indigenous communities showed that distinctive geographic location and rural lifestyles were influential factors for their insufficient access to health care facilities, 27 as well as unhealthy behaviors leading to NCD risks. 26 Thus, unhealthy practices affect indigenous peoples' health condition and status adversely.…”
Section: Indigenous People In Bangladeshmentioning
confidence: 99%
“…22 Several studies have also revealed that exposure to mass media plays an important role in the utilization of maternal health care services (MHCS) 23,24 and NCD preventive services. 25 Despite the advantageous of mass media campaigns around the world, Bangladesh is yet to realize the positive facets of mass media campaigns for changing health behaviors 26 to prevent NCDs within indigenous communities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major constraint of mHealth services is not the technical capability to handle increasing number of calls, but the limited number of physicians and medical personnel for staffing the call centres. 79 Particularly in Bangladesh, the prime challenges of mHealth management reside in identifying, recruiting, training, and retaining adequate numbers of qualified doctors. 79 Furthermore, the service has been used as a substitute for government provided healthcare, which should be an entitlement and the indigenous population should not have to rely on privately provided mHealth services.…”
Section: Research Outcomesmentioning
confidence: 99%
“…79 Particularly in Bangladesh, the prime challenges of mHealth management reside in identifying, recruiting, training, and retaining adequate numbers of qualified doctors. 79 Furthermore, the service has been used as a substitute for government provided healthcare, which should be an entitlement and the indigenous population should not have to rely on privately provided mHealth services. Such services are useful for complementing the state's responsibility to provide healthcare for all its citizens, but the indigenous people should not have to rely on it as a last resort when the public health care system fails to deliver a critical service to its citizens.…”
Section: Research Outcomesmentioning
confidence: 99%